Proceedings. ISCC 2004. Ninth International Symposium on Computers and Communications (IEEE Cat. No.04TH8769) 2004
DOI: 10.1109/iscc.2004.1358454
|View full text |Cite
|
Sign up to set email alerts
|

MUM: a middleware for the provisioning of continuous services to mobile users

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Experimental results obtained in previous work have shown that HA migration and activation at new PBs takes less than 400ms; DRCP lasts about 100ms; macro handoff flow re-direction and merging require about 500ms; global handoff flow reconfiguration requires 340ms for PS interposition and 100ms for RTP streaming activation (with a JMF server); we assume 250ms as roundtrip time [6]. In other words, handoff duration is between 440ms and 1500ms for micro handoff, about 1900ms for macro handoff, and about 2300ms for global handoff.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental results obtained in previous work have shown that HA migration and activation at new PBs takes less than 400ms; DRCP lasts about 100ms; macro handoff flow re-direction and merging require about 500ms; global handoff flow reconfiguration requires 340ms for PS interposition and 100ms for RTP streaming activation (with a JMF server); we assume 250ms as roundtrip time [6]. In other words, handoff duration is between 440ms and 1500ms for micro handoff, about 1900ms for macro handoff, and about 2300ms for global handoff.…”
Section: Resultsmentioning
confidence: 99%
“…Proxy-based middleware solutions can enhance the traditional client-to-server interaction model by decoupling the two endpoints with the insertion of an active service path [6]. Active service paths show their effectiveness when there is the need for runtime reconfiguration of only limited path segments and for decentralizing management operations to intermediate nodes traversed by service flows, thus improving scalability [12,13].…”
Section: Design Guidelines For Handoff Management Infrastructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Middleware for developing applications in ubiquitous computing environments include GAIA [26] and One.world [27]. Finally, context-aware middleware such as Migratory Services [28] and MUM [29] have been developed for mobile ad hoc networks as well.…”
Section: Related Workmentioning
confidence: 99%